Phonetic teaching materials for enhancing early childhood education teachers’ language awareness in Finland / Maria Tyrer ... [et al.] - Tyrer, Maria; Haapanen, Katja; Aerila, Juli-Anna; U. Peltola, Kimmo; S. Peltola, Maija (Universiti Teknologi MARA, Kedah, 2024)
Within the framework of language-aware pedagogy, educators in early childhood education and care (ECEC) are required to be aware of different languages and language forms, their usage and users, and the attitudes associated with them. Phonetic awareness is an important part of language awareness. This paper describes a multiprofessional cooperation project in which phonetic learning materials were created to increase ECEC teachers’ phonetic knowledge and to provide teachers with ready-made learning materials for practicing the phonetics of the Finnish language, especially in multilingual groups. The data were collected in a pedagogical intervention during which early childhood education teachers piloted the materials. The data consist of answers to an online questionnaire provided by the teachers (n = 50). This study aimed to investigate the reception and usability of the materials from versatile perspectives and as experienced by different actors in Finland’s early childhood context. The results reveal that the multiprofessional cooperation was successful in the process of developing and implementing the learning materials as they were found to be useful by all of the teachers who participated in the pilot intervention. Their applicability can be attributed to their versatility, meaning that they met the teachers’ theoretical and practical needs.